Plasma environment effects on K lines of astrophysical interest: II. Ionization potentials, K thresholds, radiative rates, and Auger widths in Ne-Through He-like iron ions (Feâ XVII-Feâ XXV) - Deprince, Jerome; Bautista, M. A.; Fritzsche, S.; Garcia, Javier; Kallman, T.; Mendoza, Claudio; Palmeri, P.; Quinet, P. (Astronomy & Astrophysics, 2019)
Aims. In the context of accretion disks around black holes, we estimate plasma-environment effects on the atomic parameters associated with the decay of K-vacancy states in highly charged iron ions, namely Feâ XVII-Feâ XXV. Methods. Within the relativistic multiconfiguration Dirac-Fock (MCDF) framework, the electron-nucleus and electron-electron plasma screenings were approximated with a time-Averaged Debye-Hückel potential. Results. Modified ionization potentials, K thresholds, wavelengths, radiative emission rates, and Auger widths are reported for astrophysical plasmas characterized by electron temperatures and densities in the ranges 105â-Â 107 K and 1018â-Â 1022 cm-3, respectively. Conclusions. We conclude that the high-resolution microcalorimeters on board future X-ray missions such as XRISM and ATHENA are expected to be sensitive to the lowering of the iron K edge due to the extreme plasma conditions occurring in accretion disks around compact objects.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Atomic data; Black hole physics; Plasmas; X-rays: general